2015
DOI: 10.1152/ajpcell.00159.2014
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory motor neurons of the esophageal myenteric plexus are mechanosensitive

Abstract: Mittal RK. Inhibitory motor neurons of the esophageal myenteric plexus are mechanosensitive. Am J Physiol Cell Physiol 308: C405-C413, 2015. First published December 24, 2014; doi:10.1152/ajpcell.00159.2014.-Mechanosensitivity of enteric neurons has been reported in the small intestine and colon, but not in the esophagus. Our earlier in vivo studies show that mechanical stretch of the esophagus in the axial direction induces neurally mediated relaxation of the lower esophageal sphincter, possibly through mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 46 publications
5
26
0
Order By: Relevance
“…Second, the mechanosensitivity of NCX1 may play a functional role in the EMN since the latter is subjected to mechanical distortion that could activate NCX1 during oesophageal motility. Third, in a study, 15 we found that mechanical stretch induced Ca 2+ -dependent NO production in the EMN, which is consistent with other reports that show flow-dependent changes in the NCX activity modulates endothelial NO production. 52 Based on the fact that operation of the Ca 2+ entry mode of NCX1 raises [Ca 2+ ] cyt and that nNOS is a Ca 2+ -dependent enzyme, NCX1 would produce NO production in the EMN.…”
Section: F I G U R E 6 Immunocytochemistrysupporting
confidence: 92%
See 3 more Smart Citations
“…Second, the mechanosensitivity of NCX1 may play a functional role in the EMN since the latter is subjected to mechanical distortion that could activate NCX1 during oesophageal motility. Third, in a study, 15 we found that mechanical stretch induced Ca 2+ -dependent NO production in the EMN, which is consistent with other reports that show flow-dependent changes in the NCX activity modulates endothelial NO production. 52 Based on the fact that operation of the Ca 2+ entry mode of NCX1 raises [Ca 2+ ] cyt and that nNOS is a Ca 2+ -dependent enzyme, NCX1 would produce NO production in the EMN.…”
Section: F I G U R E 6 Immunocytochemistrysupporting
confidence: 92%
“…12 More recently, we successfully cultured the EMN from the rat oesophagus. 14 Using the EMN grown in primary culture as cell model, we found that the oesophageal inhibitory motor neurons possessed mechanosensitive properties, 15 that is, they responded to osmotic and mechanical stretch, which was similar to the findings of Mazzuli and Schemann in the small intestine and colon. 7,16 However, so far there is almost no information on the nature of molecules responsible for the mechanosensitivity of enteric neurons.…”
supporting
confidence: 78%
See 2 more Smart Citations
“…Several studies have reported distinct mechanosensitive responses in enteric neurons to tensile stress (stretch), compressive stress (volume injection, glass probe, or von Frey hair), shear stress, and cell swelling (hypoosmotic solutions) (Dong, Jiang, Dong, & Mittal, 2014; Hibberd, Zagorodnyuk, Spencer, & Brookes, 2012; Kugler et al, 2015; Kunze et al, 1999; Kunze, Clerc, Furness, & Gola, 2000; Kunze et al, 1998; Mayer & Wood, 1975; Mazzuoli & Schemann, 2009, 2012; Spencer & Smith, 2004). While these studies suggest roles in mechanosen-sitivity sensing and control of muscle activity, as well as a servo-feedback loop (Mazzuoli-Weber & Schemann, 2015), the identities of the mechano-sensitive ion channels responsible for mechanotransduction are largely unknown.…”
Section: Mechanosensitive Ion Channelsmentioning
confidence: 99%